Factors associated with social network addiction in college students: a systematic review and meta-analysis - Basauri Delgado, Miguel Angel (2023)
Addiction to social networks has increased throughout the COVID-19 outbreak, especially within the university context, due to its continuous use for socialization, entertainment, education, and work. The study aimed to carry out a systematic review and meta-analysis of the factors associated with addiction to social networks in university students. A search in the Scielo, Eric, PubMed, and Science Direct databases found 31 articles that met the inclusion and exclusion criteria and analyzed a total sample of 13 028 university students. The articles presented 91 variables associated with addiction to social networks; these were grouped into nine categories to perform the meta-analysis, which revealed six categories with a direct relationship (online factors = .41, cognitive factors = .41, negative symptomatology = .30, addiction and cell phone use = .29, network use = .21, social factors = .29), one with an inverse relationship (positive emotions = -.14) and two that do not have significant values (academic factors = .01 and personal skills = .06). The study concludes that there is a stronger relationship between online factors and cognitive factors with addiction to social networks.